2011
DOI: 10.1007/s10876-011-0422-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of O2 Adsorption Stability and Strength Over Gold Clusters Using DFT and Logistic Regression

Abstract: In this work, the stability and strength of O 2 adsorption over Au 2-10 clusters were studied. The density functional theory (DFT) computed adsorption data were classified using multiple logistic regression. The effects of user defined descriptors were analyzed and it was found that stable O 2 adsorption requires the presence of an unpaired electron while its strength depends on the size and the charge of the cluster. As the size of the cluster increases, the probability of strong adsorption decreases, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…The interaction of the gold cluster with O 2 has been an active field in both experimental and theoretical research studies because this interaction is important for understanding the remarkable catalytic effects discovered for the metal nanoparticles. , Cox et al , were the first to report the experimental work for O 2 adsorbed on a series of gold cluster Au n q with n = 3–20 and q = +1, 0, −1. Günay et al investigated O 2 adsorption on a gold cluster and found that stable O 2 adsorption required the presence of an unpaired electron on the gold cluster. Lee et al , calculated O 2 and O adsorption on Au 38 and found that the most stable sites for O 2 and O adsorption are the bridge and hexagonal sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of the gold cluster with O 2 has been an active field in both experimental and theoretical research studies because this interaction is important for understanding the remarkable catalytic effects discovered for the metal nanoparticles. , Cox et al , were the first to report the experimental work for O 2 adsorbed on a series of gold cluster Au n q with n = 3–20 and q = +1, 0, −1. Günay et al investigated O 2 adsorption on a gold cluster and found that stable O 2 adsorption required the presence of an unpaired electron on the gold cluster. Lee et al , calculated O 2 and O adsorption on Au 38 and found that the most stable sites for O 2 and O adsorption are the bridge and hexagonal sites.…”
Section: Resultsmentioning
confidence: 99%
“…27,78−90 Cox et al 91,92 were the first to report the experimental work for O 2 adsorbed on a series of gold cluster Au n q with n = 3−20 and q = +1, 0, −1. Gunay et al 93 investigated O 2 adsorption on a gold cluster and found that stable O 2 adsorption required the presence of an unpaired electron on the gold cluster. Lee et al 94,95 calculated O 2 and O adsorption on Au 38 and found that the most stable sites for O 2 and O adsorption are the bridge and hexagonal sites.…”
Section: Resultsmentioning
confidence: 99%